Comparative Effectiveness of Bangla and English Language Mnemonics in Short Term Memorization of Anatomical Information by Bengali Medical Undergraduates (Bangladesh Journal of Medical Education, 2026)
Background: Use of mnemonics can assist to learn anatomical information more quickly and native language always positively stimulates learning. Objective: The study aimed to explore the effectiveness of Bangla and English language mnemonics in short term memorization by the Bangladeshi medical undergraduates. Method: A total of 93 first-year Bangladeshi medical undergraduates of a public medical college of Dhaka city were selected by convenient sampling and divided into three groups (Bangla, English and Control). They were instructed to follow the guidelines given at the beginning regarding use of mnemonics on their assigned groups. After half an hour an assessment was taken. Result: Use of Bangla was found significantly more effective than English. Both Bangla and English language mnemonics were significantly more effective than control group where no mnemonics were used. Conclusion: Mnemonics can help to reduce cognitive loads of the learners in short time memorization in irrespective of its linguistic expression.BJME: Vol.-17, Issue-02, July, 2026: 3-11